Do accounting skills help in the sustainable development of SMEs? / Muraddin Purag, Rozita @ Uji Mohammed and Sheikh Junaidi Sheikh Mohammad. - Purag, Muraddin; Mohammed, Rozita @ Uji; Sheikh Mohammad, Sheikh Junaidi (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2018)
SMEs play an important role in the economy and development of a country as they dominate every business sector in the world, it is estimated that more than 95% of enterprises in the world are SMEs. World Economic Forum 2015 reported that SMEs contributed 50% and 40% of GDP in high-income economies and emerging economies respectively. In 2010, Malaysia recorded 97.3% establishment of SMEs from the overall business ecosystem, majority of the SMEs establishments are classified as microenterprise (76.5%) and followed by small (21.2%) and medium (2.3%), this suggests that SMEs play an important role in the economic development of a country, especially Malaysia. However, one thing to worry about is the sustainability of SMEs in open competition, as more than 50% of SMEs close their business within 5 years of its operation, in Malaysia the rate is even higher, with more than 60% failure rates within 5 years of operation. Various causes of SMEs failure in business have been identified by various government agencies and researchers, one of the causes is the lack of accounting skills, especially in record keeping that will limit their access to the loan or financial aids available for SMEs. The basic accounting skill needed by the SMEs entrepreneurs is bookkeeping, this is because without a proper record, it is hard for them to get an access to loans or financial aids provided by the government agency because most of the financing are provided to the entrepreneurs that are already in the business and the assessment is based on their financial records, the lack of financial records is among the reasons why SMEs will miss out on the financial aid from the government agencies. Besides, the entrepreneurs also need to equip themselves with the cost accounting skill in order for them to understand the costing of a product so that they will not tend to overprice or under-price their products. Most of the small entrepreneurs are unable to understand the cost structures of their products, thus failing to control the cost of their products and unable to apply the appropriate pricing structures to their products. The aim of the paper is to assess whether the accounting skill among entrepreneurs will assist in the SMEs sustainability. This paper provides a deep review and analysis on whether the accounting skills possessed by the entrepreneurs will help to sustain their businesses in the long run despite the challenges faced by the businesses, the papers focused on the SMEs since, this group dominate the business community.